Swot Strategy Analysis in Improving the Quality of Public Services During the Covid-19 Pandemi (Study at Pekon Soponyono, Wonosobo District, Tanggamus Regency) - susilawati; Eny Inti Suryani; Sindi Sanora (LEGAL BRIEF, 2022)
This study aims to find out how the SWOT Strategy Analysis is in Improving the Quality of Public Services during the Covid-19 Pandemic in Pekon Soponyono, Wonosobo District, Tanggamus Regency. This research uses a qualitative descriptive method. With SWOT data analysis techniques, SWOT analysis is carried out using the Internal Factory Analysis Summary matrix. (IFAS) and External Factory Analysis Summary (EFAS) to find out which strategies are suitable for use in Pekon Soponyono. This research resulted in findings that the public services provided by Pekon Soponyono seen from public service standards which include service procedures that are still difficult for the community to understand, existing facilities and infrastructure are inadequate so that this hinders the service process and the competence of service providers still needs to be improved because background factors are also one of the causes of a lack of understanding of the service process and the absence of special training for apparatus to develop their potential. The SWOT analysis produces a WO (Weakness-Opportunities) strategy, namely establishing a strategy for simplifying service procedures so that the services provided can be effective and efficient, improving facilities and infrastructure considering the need for higher services.